Measuring the knowledge about science in student’s learning achievement - Yadamjav, Munkhsaikhan; Chuluunkhuu, Enkhlut; Battsogt, Bulgamaa; Banzragch, Burmaa (Scientific transaction of the National University of Mongolia. Physics, 2022)
Since 2000, The Organisation for Economic Co-operation and Development (OECD) Programme for International Student Assessment (PISA) has been aiming to provide understanding of students’ learning achievement within the wider educational community [2]. In order to achieve the goal, they have defined that scientific literacy consists of “Knowledge of science” and “Knowledge about science”. The latter refers to the knowledge of the skills (scientific enquiry) and the goals (scientific explanation) of science. This article introduces how we used probability and statistics to assess the knowledge in order to provide a general direction for policy makers in educational systems.